EXPANSION OF JIJEL CITY AND THE PROBLEM OF URBAIN SPATIAL COHERENCE - Boulkroune Fatima Zohra; Hammoud Naima (International Journal of Innovative Technologies in Social Science, 2024)
Through an assessment of the level of urban coherence in the city of Jijel, it was concluded that the city suffers from a lack of coherence in its urban components. Despite the existence of several laws related to urban planning and development, there are widespread urban violations and a significant prevalence of informal settlements in the city’s urban environment. This is due to a lack of continuous monitoring by the relevant authorities and a lack of awareness of urban planning and construction laws among citizens. Some citizens even circumvent the laws. To achieve urban coherence in the city, citizens must adhere to legislative laws, and local authorities must impose strict penalties on anyone who violates or contravenes urban planning and construction laws. Additionally, it is recommended to propose projects that would give the city a coherence appearance, such as an urban coherence plan.